Prevalence, and outcomes of rheumatic heart disease in ethiopia: a systematic review and meta-analysis - Dhodho, Munyaradzi (Department of Public Health and Family Medicine, 2026)
Background: While eradicated in other parts of the world, Rheumatic Heart Disease, nevertheless, remains one of the most common acquired heart diseases in low- to middle- income countries; in sub-Saharan Africa, there was an estimated prevalence of 10 persons per 1,000 population in 2015. In the Global Burden of Disease estimates 1990-2015, Ethiopia was identified as having one of the highest burdens of RHD with a prevalence of 100-149 persons per 100,000 population. We therefore sought to estimate the prevalence of RHD, and clinical and post-operative outcomes, in Ethiopia. Objectives: We conducted a systematic review of the prevalence and outcomes of RHD according to a priori protocol. Data Sources: Studies included in this review were retrieved from PubMed and Web of Science. In addition, Google Scholar and approaching authors was used to complement the search. Data Extraction: Studies conducted after 2012 were included if the method of RHD diagnosis was echocardiography. A meta-analysis was done to measure the pooled prevalence and outcomes of RHD. Results: A total of nine studies were included in this review, 5 focusing on prevalence and 4 focusing on outcomes of RHD. The overall prevalence of asymptomatic echocardiographic RHD was per 21 per 1000 (95% CI, 12.27;32.03). In hospitalised patients, presentation included congestive heart failure, atrial fibrillation, and stroke. The 30-day mortality and post- operative mortality was 2.5 (95% CI, 0.00;12.81) and 32.8 (95% CI, 11.43;62.82) per 1000 respectively. The 60-day mortality and post-operative mortality was 33.5(95% CI, 0.00;111.38) and 161.7 (95% CI 125.54;201.27) per 1000 respectively. Conclusions And Relevance: The prevalence of asymptomatic RHD in Ethiopia is high while RHD in adults/children is associated with congestive heart failure, atrial fibrillation, and stroke. Mortality was high in patients with RHD-related heart failure; thus, to achieve the World Heart Federation target of a 25% reduction in the mortality due to RHD by 2025 in the under 25- year-olds might prove challenging.